THE BIOPOLITICS OF MENSTRUATION IN HUNGARY: THEN AND NOW - Sándor, Judit (Pravni zapisi, 2025)
This article focuses on postwar Hungary, including the transition from state socialism to peripheral capitalism. This era is especially important as during the decades of cold war one of the main claims was that social and welfare rights – including the right to healthcare – were exemplary in state socialism and much more advanced than in the capitalisms of the West. This article argues, however, that even though social welfare rights were advanced in certain jurisdictions and fields, they did not eradicate patriarchal views. Neglecting women during their pe- riod also shows that protecting motherhood did not automatically increase women’s rights. While women’s welfare rights have been underdeveloped, there have been some significant achievements in the fields of maternal care and childcare.
Keywords: Menstruation; Stigma; Discrimination; Tampon; Clinical Trials; Cold War; Healthcare; State Socialism; Hungary